PENGARUH BUDAYA TOLERANSI KEKUASAAN TERHADAP PERSEPSI KARIR BIROKRATIK DAN PROFESIONAL (STUDI EMPIRIK PADA PROFESI PERAWAT RS. ISLAM SULTAN AGUNG SEMARANG) - Rahayuningsih, Sri (Proceeding SENDI_U, 2020)
Organization culture is collection of positive value that is useful for organization in order to influencebehavior. Authority tolerance culture is part of culture concept founded by Hofstade (1994). As high as authorityto culture, means they are willing to accept the authority to culture difference in an organization. Careerperception is perception as long as working (Asthur, et al, 1989. The aim of this research are to analyze and toprove whether tolerant culture influence bureaucratic and professional career perception.Method of this research uses purposive sampling method with 89 female nurse as samples and also uses doubleregression analysis. Result of this research shows that authority tolerance culture has positive influence towardsbureaucratic to career perception and professional career perception. It means that as high as authority toleranceculture will determine life someone’s career choice, even though still in perception form. Next, this perceptionwill influence someone’s behavior in acting to do pioneering career.